Evaluation of anti-Fusarium and auxin production of Trichoderma virens InaCC F1030 isolated from rhizosphere of banana - Toga Pangihotan Napitupulu; Indriati Ramadhani; Atit Kanti; I Made Sudiana (Journal of Microbial Systematics and Biotechnology, 2020)
Banana rhizosphere harbors a unique diversity of microbes including fungi that play critical roles in the growth of the plant host as well as might be important for biologically controlling the fungal soil-borne pathogens particularly Fusarium oxysporum f.sp. cubense (Foc), the causing agent of devastating Panama wilt. Among other fungi, we have succeeded to isolate a Trichoderma species from rhizosphere of healthy banana. Molecular identification revealed the isolate as Trichoderma virens InaCC F1030 (being collection of Indonesian Culture Collection or InaCC). Therefore, the aim of this study was to investigate the biological control of our isolate against Foc as well as plant growth promoting ability through its ability to produce auxin (indole-3-acetic acid/IAA). Two approaches were employed to evaluate the antagonism of our isolate against Foc, through direct confrontation test and volatile organic compounds (VOCs) producing. We found that our isolate was considered as antagonistic to the Foc, but not highly antagonistic according to direct confrontation assay. However, it was also revealed that our isolate produces the VOCs that inhibited around 50% of the mycelial growth of the test pathogen after six to seven days of exposure. Our isolate was able to produce the IAA in axenic submerged fermentation condition particularly in the presence of the precursor L-tryptophan. IAA production ability as well as the mycelial biomass of fungus were increased approximately 17% and 120% respectively as the effect of supplementation of 0.1% of L-tryptophan. These in vitro bioassays lead us to conclude that somehow our isolate T. virens InaCC F1030 has potency to be utilized as biocontrol and biofertilizer agent.